Strategic Command Taking the Long View for Organizational Success - Beatty, Katherine; Beatty, Katherine; Quinn, Laura (Center for Creative Leadership, 2002)
Organizations can best gain an advantage over their competitors by practicing strategic leadership. But how is strategic leadership accomplished, and who in an organization should be responsible for it? Strategic leadership is a complex process of thinking, acting, and influencing, and it can be exercised not just by individuals but also by teams.